2011
DOI: 10.1111/j.1365-2044.2011.06812.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethnicity and body mass index on the distance from skin to lumbar epidural space in parturients

Abstract: SummaryWith the current prevalence of obesity and trends in ethnic diversity amongst parturients in UK maternity units, we performed a prospective, observational study to establish the effect of ethnicity and body mass index on the distance from skin to epidural space in parturients. A total of 1210 parturients participated in this study. The mean (SD) distance from skin to lumbar epidural space was 5.4 (1.1) cm. When tested in a multiple regression model, both body mass index and ethnicity significantly influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
(23 reference statements)
3
19
0
1
Order By: Relevance
“…Thirteen studies were from the UK (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), three from Australia (40,41), two from Norway (42,43) and Canada (44,45), and one from USA (46) and Spain (47) ( Table 1). Some studies used more than one exposure: 21 studies used maternal anthropometric measurements as the exposure (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(43)(44)(45)(46)(47)(48) (group 1), three used gestational change in maternal anthropometrics as the exposure (31,42,47) (group 2) and two used a combination of pre-pregnancy anthropometrics and gestational change in anthropometrics (42, 43) (group 3). Of the studies that used maternal BMI as a categorical exposure (n = 7), only three studies applied BMI criteria for South Asian populations (29,46,48).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirteen studies were from the UK (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), three from Australia (40,41), two from Norway (42,43) and Canada (44,45), and one from USA (46) and Spain (47) ( Table 1). Some studies used more than one exposure: 21 studies used maternal anthropometric measurements as the exposure (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(43)(44)(45)(46)(47)(48) (group 1), three used gestational change in maternal anthropometrics as the exposure (31,42,47) (group 2) and two used a combination of pre-pregnancy anthropometrics and gestational change in anthropometrics (42, 43) (group 3). Of the studies that used maternal BMI as a categorical exposure (n = 7), only three studies applied BMI criteria for South Asian populations (29,46,48).…”
Section: Resultsmentioning
confidence: 99%
“…We also searched citations and reference lists of included studies, and the reference lists of reviews that were related to the topic area. Of the 22 included studies, 20 were identified through database search alone (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(42)(43)(44)(45)(46)48), one from screening the reference lists of relevant reviews (41) and one from searching the citations of included studies (47). In their recent review and meta-analysis, Heslehurst et al also found that in order to minimize bias, it was essential to include evidence from searches in addition to database searching (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Sharma reported that ethnicity was related to epidural depth and BMI, possibly related to body shape 9 ; however, the body shapes of the investigated women according to ethnicity were not reported. 22,23 Only 27% of the women had all four reviewers' agreement regarding body shape. Traditional body shape allocation is done with front and side views 9 ; however, we used back views, congruent with anesthesia providers' observations prior to neuraxial block placement, and the pregnant belly likely distracts from shape categorization using side views.…”
Section: Discussionmentioning
confidence: 99%
“…Il mesure quelques millimètres dans son axe antéro-postérieur (0,9 cm ± 0,5) et cette distance augmente avec l'IMC [10]. Bien que la distance peau-EPD augmente avec l'IMC [10,11], elle est en moyenne de 5 à 7 cm [10,11] chez la majorité des parturientes obèses. L'utilisation d'une aiguille de Tuohy de taille standard (90 mm) reste donc recommandée.…”
Section: Recherche De L'epd Difficile : Nombreux Faux Positifsunclassified